2009
DOI: 10.1001/archsurg.2008.591
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Stapled Hemorrhoidopexy vs Conventional Hemorrhoidectomy

Abstract: Stapled hemorrhoidopexy is a safe technique for the treatment of hemorrhoids but carries a significantly higher incidence of recurrences and additional operations compared with CH. It is the patient's choice whether to accept a higher recurrence rate to take advantage of the short-term benefits of SH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
126
3
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(144 citation statements)
references
References 54 publications
10
126
3
5
Order By: Relevance
“…The absence of local care and less postoperative pain are clear advantages to the patient. SH results in significantly lesser immediate postoperative pain than conventional excision techniques (by 2 to 3 levels on Visual Analogue Scale) and offers more comfort to the patient [22,23]. Similarly, a high level of patients' satisfaction was achieved in the current study in terms of low incidence of pain and complications.…”
Section: Discussionsupporting
confidence: 64%
“…The absence of local care and less postoperative pain are clear advantages to the patient. SH results in significantly lesser immediate postoperative pain than conventional excision techniques (by 2 to 3 levels on Visual Analogue Scale) and offers more comfort to the patient [22,23]. Similarly, a high level of patients' satisfaction was achieved in the current study in terms of low incidence of pain and complications.…”
Section: Discussionsupporting
confidence: 64%
“…Other studies observed reduced post-operative pain [19,25] and also, in systematic reviews and meta-analyses relief of postoperative pain was observed after SH procedure [10,11,13]. Similarly, we have observed 96 % pain relief at 1 year follow up.…”
Section: Discussionsupporting
confidence: 85%
“…As mentioned earlier, the early clinical trials have shown the safety and effectiveness of the SH procedure. The clinical effectiveness have been proved by showing minimal post-operative pain, shorter hospital stay, early to resume the work, shorter operative time, and acceptable safety profile [10][11][12][13][14][15][16]. Many of the studies [18][19][20][21][22] reported the average length of operation time was around 25 minutes, highlighting the saving time as compared to conventional surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis of long-term outcomes of SH versus CH demonstrated a significantly higher overall rate of prolapse recurrence in the SH group [8]. The difference was even more significant in the subset of patients with III and IV degree haemorrhoids.…”
mentioning
confidence: 98%